PENGEMBANGAN ALAT PERAGA LISTRIK DINAMIS (APLD) BERBASIS INKUIRI UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA - Muhammad Azhari Hasbi; Kosim -; Gunawan - (Postgraduate, University of Mataram, 2015)
In this study has been developed a teaching aid of dynamic electricity(APLD) inquiry based to support dynamic electricity of learning. This study included research development. The purpose of this study was to develop and test the effectiveness of the teaching aid to increase mastery of concepts of students. The study involved IX grade of junior students who were following the dynamic electricity of learning were divided into two groups, namely the experimental group and the control group. The instrument used was the dynamic electric concept mastery test. Analysis of data using different test and the average normalized gain scores . This study showed an increase in mastery of concepts in both groups. The Increase concepts mastery of students using APLDinquiry-based was higher than students who studied the electrical KIT with verification based-guide. The increase was highest in the mastery of concept Ohm's Law (69.3 %) and the lowest was in the electric power concept (10.8 %) Keyword: Teaching aid of dynamic electricity (APLD) inquiry based, mastery of concepts dynamic electricity.